2023
DOI: 10.3390/jcs7110460
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Applicability of Modifying CdSe Thin Films by the Addition of Cobalt and Nickel to Enhance the Efficiency of Photocatalytic Decomposition of Organic Dyes

Aliya Zh. Omarova,
Talgatbek Ayazbaev,
Zhanar S. Yesdauletova
et al.

Abstract: This article presents the results of an assessment of the use of CdSe, NiCdSe, and CoCdSe thin films as a basis for photocatalysts used for the decomposition of the organic dyes rhodamine B, cargo red, and indigo carmine. Interest in this area was determined by the need to solve a number of issues related to increasing the efficiency purifying aqueous media from the negative effects of organic dyes, which cannot be disposed of using traditional methods associated with adsorption or filtration. The use of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Wan et al [13] performed an investigation on NiCo 2 O 4 catalyst preparation for the degradation of methyl red under visible light irradiation, and they found that the methyl red photodegradation efficiency of mesoporous NiCo 2 O 4 can reach 95.1% under visible light irradiation for 2 h. Additionally, the demonstrated effectiveness of NiCo 2 O 4 in photodegradation within the visible region has enhanced the popularity of this mixed oxide compound, mainly due to its multiple valence states, hypotonicity, ultrastability, and containable structure [12]. To further enhance the properties of NiCo 2 O 4 , one typical method that has gained popularity over recent years is performing transition metal doping onto a semiconductor film [14,15]. Han et al [16] synthesized Cu-doped NiCo 2 O 4 nanosheets using a thermal method for energy storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al [13] performed an investigation on NiCo 2 O 4 catalyst preparation for the degradation of methyl red under visible light irradiation, and they found that the methyl red photodegradation efficiency of mesoporous NiCo 2 O 4 can reach 95.1% under visible light irradiation for 2 h. Additionally, the demonstrated effectiveness of NiCo 2 O 4 in photodegradation within the visible region has enhanced the popularity of this mixed oxide compound, mainly due to its multiple valence states, hypotonicity, ultrastability, and containable structure [12]. To further enhance the properties of NiCo 2 O 4 , one typical method that has gained popularity over recent years is performing transition metal doping onto a semiconductor film [14,15]. Han et al [16] synthesized Cu-doped NiCo 2 O 4 nanosheets using a thermal method for energy storage applications.…”
Section: Introductionmentioning
confidence: 99%